Effects of Ralgro® implants from birth to slaughter on performance, masculinity, and behavior of young bulls - Gray, D.G.; Unruh, John A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Implanting bulls with Ralgro® from birth to slaughter resulted in performance similar to that of nonimplanted bulls. However, implanted bulls were less masculine, had smaller scrotal circumference up to 16 months of age, had lower serum testosterone levels up to 13 months of age, and were less aggressive from 12 to 14 months of age compared to nonimplanted bulls.
Keywords: Beef; Implants; Performance; Masculinity; Behavior; Bulls